2016
DOI: 10.12968/bjcn.2016.21.4.188
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of people living with Parkinson's disease: a qualitative study in Iran

Abstract: The study results showed that older adults with PD face a number of challenges in self-care. In addition, the 'fear of becoming disabled' was the main concern of patients with PD, particularly in late stages of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
1
16
1
Order By: Relevance
“…59 Soleimani et al revealed that people living with Parkinson's were concerned about losing social connectedness because of their disease (preventing them from leaving the house or increasing their desire to remain isolated to conceal symptoms). 60 Reduced social outings were found to greatly influence QoL and functioning in other relationships (eg, couple and family). 23,61 Fleming et al reported a divide in how friendships changed with PD.…”
Section: Friendship Rolementioning
confidence: 99%
See 3 more Smart Citations
“…59 Soleimani et al revealed that people living with Parkinson's were concerned about losing social connectedness because of their disease (preventing them from leaving the house or increasing their desire to remain isolated to conceal symptoms). 60 Reduced social outings were found to greatly influence QoL and functioning in other relationships (eg, couple and family). 23,61 Fleming et al reported a divide in how friendships changed with PD.…”
Section: Friendship Rolementioning
confidence: 99%
“…4,54,59,60 Rubenstein et al noted that although the number of visits friends made to people living with Parkinson's remained the same, people living with Parkinson's were less likely to initiate social outings with friends. 60 Reduced social outings were found to greatly influence QoL and functioning in other relationships (eg, couple and family). 60 Reduced social outings were found to greatly influence QoL and functioning in other relationships (eg, couple and family).…”
Section: Friendship Rolementioning
confidence: 99%
See 2 more Smart Citations
“…Changing identity, self-worth and purpose falls into the life experience of PD patients, forming the basis of their decisions and behaviours (Bramley and Eatough, 2005; Gibson and Kierans, 2017; Olsson and Nilsson, 2015;Sheehy et al, 2016;Simpson et al, 2015;Sunvisson, 2006). In a chronic disease such as PD, perceptions and attitudes of individuals toward themselves are considered to have an important influence on the quality of self-care behaviours (Soleimani et al, 2016). In this study, patients with negative self-concepts became more passive in their self-care over time.…”
Section: Discussionmentioning
confidence: 72%